A tutela do direito à saúde e a integração legislativa da Constituição Federal: uma investigação de efetividade do Poder Judiciário sob a ótica do Conselho Nacional de Justiça - Mendes Neto, João Paulo (2013)
This work aims to present the principle of the separation of Powers as a base premise to justify the effectuation of social rights by the Judicial Power. This study also objectives to define and justify the social rights as true fundamental rights, in a manner that recognizes, as civil and political rights, an immediate applicability given by the Citizen Constitution of 1988. Established these presuppositions, this work defends the capacity of the Judicial Power to function as a form to give effectiveness to social guarantees, especially, to the right of health, despite recognizing that it does not belong only to that Power ensure such effectiveness. This analysis is made by the decisions of the Brazilian Supreme Court and the philosophical justifications invoked, which will lead to the legitimacy of this Power to act in the defense of fundamental rights. This legitimacy will also be questioned to the National Council of Justice (NCJ), verifying through its constitutional functions until what point this Council should and could act in the effectuation of these rights as a representative of the Judicial Power in a non-legal manner so that there is a much greater uniformity between the budget legislation and the Federal Constitution and consequently, with the effective guarantee of fundamental rights. Finally, it is defended that the structure of the Federal Constitution allows the affirmation that the Brazilian State is turned to the ultimate reason to improve the social reality affected by the lack of recognition of these rights to society and that such a function could perfectly well be of the NCJ